Neuroprotective compounds from marine invertebrates - Bachtiar Rivai; Abd. Kakhar Umar (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background Neuroinflammation is a key pathological feature of a wide variety of neurological disorders, including Parkinson’s, multiple sclerosis, Alzheimer’s, and Huntington’s disease. While current treatments for these disorders are primarily symptomatic, there is a growing interest in developing new therapeutics that target the underlying neuroinflammatory processes. Main body Marine invertebrates, such as coral, sea urchins, starfish, sponges, and sea cucumbers, have been found to contain a wide variety of biologically active compounds that have demonstrated potential therapeutic properties. These compounds are known to target various key proteins and pathways in neuroinflammation, including 6-hydroxydopamine (OHDH), caspase-3 and caspase-9, p-Akt, p-ERK, p-P38, acetylcholinesterase (AChE), amyloid-β (Aβ), HSF-1, α-synuclein, cellular prion protein, advanced glycation end products (AGEs), paraquat (PQ), and mitochondria DJ-1. Short conclusion This review focuses on the current state of research on the neuroprotective effects of compounds found in marine invertebrates and the potential therapeutic implications of these findings for treating neuroinflammatory disorders. We also discussed the challenges and limitations of using marine-based compounds as therapeutics, such as sourcing and sustainability concerns, and the need for more preclinical and clinical studies to establish their efficacy and safety. Graphical abstract